Chartism and the Chartists in Manchester and Salford - Pickering, P. author. aut Link
X, 294 p.
Keywords: In 1845 Frederick Engels wrote that 'Manchester is the seat of the most powerful unions, the central point of Chartism, the place which numbers the most Socialists'. There have been many local studies of the Chartist struggle for democratic political reform, but there is no major study of the movement in the Manchester-Salford conurbation, its most important provincial centre. This book brings an innovative approach to an exploration of aspects of the Chartist experience in the 'shock city' of the industrial revolution.